Rapid-Sequence Intubation - Evangelina Dávila Cabo de Villa; Rosendo López González; Fernando Márquez Ercia; Carlos M. Hernández Dávila (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
In medical practice there are several situations that require immediate intervention of the airway in some patients, in order to ensure proper entrance and exit of gases into and out of the lungs and prevent aspiration. Rapid-sequence intubation has been considered as the administration of a hypnotic agent and a neuromuscular relaxant consecutively (virtually simultaneously) to facilitate orotracheal intubation in critically ill patients and minimize the risk of aspiration. This paper aims to collect elements that promote a successful medical management according to the situation presented, since there is no single way of proceeding in case of rapid-sequence intubation. The elements to consider include: knowing the anatomy of the upper respiratory tract, having a group of drugs to choose from, receiving adequate training and having an alternative plan for the difficulties that may arise.